Outlaw heroes as liminal figures of film and television - Umland, Rebecca A. (McFarland & Company, Inc., Publishers, 2016)
"This book examines the liminal outlaw hero's origins in medieval romance, his survival in the mythology of the Hollywood western and his incarnations in the urban Western and modern action film. "...